Environment-friendly starch size for sizing glass fiber yarn for high-density weaving as well as preparation method and application of environment-friendly starch size

By modifying amphiphilic starch and combining textile additives, an environmentally friendly starch slurry suitable for high-density woven glass fiber yarns was prepared, which solved the problem of poor performance of traditional slurry in high-density weaving and achieved high bundling , the improvement of wear resistance and mechanical properties is in line with the concept of green development.

CN119265931APending Publication Date: 2025-01-07JIANGSU NEW REBA TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411246097.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to provide slurry suitable for high-density weaving glass fiber yarns, and cannot have high bundle properties, high wear resistance, high elasticity and excellent mechanical properties, and the adhesion performance of traditional starch slurry is not ideal.

Method used

Through the preparation of amphiphilic starch, including starch refining, acidolysis, hydrophobic modification and functional monomer modification, combined with an appropriate amount of plasticizer, binder, wetting agent and antistatic agent, an excellent viscosity and Environmentally friendly starch slurry with surface tension, used for high-density woven glass fiber yarn sizing.

Benefits of technology

The high-bundleability, wear resistance, elasticity and mechanical properties of high-density woven glass fiber yarn have been improved, the amount of textile additives is reduced, the slurry stability and environmental protection are improved, and the requirements of high-density weaving are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265931A_ABST
    Figure CN119265931A_ABST
Patent Text Reader

Abstract

The invention relates to environment-friendly starch slurry for sizing glass fiber yarns for high-density weaving as well as a preparation method and application of the environment-friendly starch slurry, and belongs to the technical field of textile weaving. The method disclosed by the invention comprises the following steps: preparing specific amphiphilic starch through starch refining, starch acidolysis, hydrophobic modification and functional monomer modification; gelatinizing starch; adding a specific plasticizer, a binder, a wetting agent and an antistatic agent combination into the starch slurry, heating and uniformly mixing, and cooling to obtain the environment-friendly starch slurry for sizing the glass fiber yarns for high-density weaving; according to the environment-friendly starch size for sizing the glass fiber yarn for high-density weaving and the preparation method of the environment-friendly starch size, the starch serves as a main film-forming agent, and the size has appropriate viscosity and surface tension and excellent size stability and is applied to sizing of the glass fiber yarn for high-density weaving; the sizing rate is high, and the processed product has high bundling property, high wear resistance, high elasticity, excellent mechanical property and excellent flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an environmentally friendly starch slurry for sizing glass fiber yarn for high-density weaving and a preparation method and application thereof, belonging to the technical field of textile weaving. Background Art

[0002] Glass fiber yarns used for textiles are usually composed of hundreds of parallel continuous long fibers, which are processed by untwisting and twisting a bundle of raw yarns or multiple bundles of raw yarns formed by an impregnation agent. When used as warp yarns, they are guided around the back beam, pass through the drop wire, heald eye and reed in a specific order, and finally gather at the cloth fell, bypass the breast beam, and wind onto the cloth roller. During this process, the warp yarns are in close contact with various parts of the loom. With the five basic movements of the loom, relative friction is generated between the glass fiber and these parts. This friction and wear is one of the key factors affecting the quality of the fabric and runs through the entire yarn weaving process. Due to repeated friction, the protective layer of the impregnation agent on the surface of the glass fiber is destroyed, resulting in grinding, cutting and pulling off on the fiber surface, which in turn causes single fiber breakage, loose yarn structure, reduced strength and increased hairiness. These longer hairiness not only aggravates the friction of the warp yarn, but also may stick to each other, and even entangle with the teeth of the steel reed and the adjacent warp yarn to form hair balls, resulting in unclear openings, thus hindering the smooth weaving process. In order to prevent the generation of hairiness during the weaving process from affecting the quality of the fabric and improve the production efficiency of the weaving, the glass fiber warp yarn needs to be secondary sized before weaving to increase the strength and wear resistance of the warp yarn and reduce the generation of hairiness.

[0003] High-density weaving glass fiber yarn is different from ordinary weaving glass fiber yarn in that it is more difficult to produce. First, the yarn diameter is small, the number of cross-sectional fibers is small, and the warp yarn absorption rate is low during sizing. Second, it is difficult for the product to have high bundling, high wear resistance, high elasticity, excellent mechanical properties and excellent softness.

[0004] In industrial production, the main sizing agents used for glass fiber yarns include polyacrylate, polyvinyl alcohol (PVA) and modified ester starch. Among them, PVA sizing is widely used in textile sizing due to its excellent fiber bundling performance and high strength, but its difficulty in desizing and greater environmental pollution problems limit its scope of use. Modified ester starch, as a widely available renewable natural resource, is often used as a film-forming agent due to its good adhesion and biodegradability. It is easy to desize after sizing, which helps to reduce pollution and energy consumption. However, due to the high viscosity of native starch and its low affinity for glass fiber, it cannot be directly used for sizing of glass fiber. Therefore, it is necessary to modify the starch and then combine it with textile auxiliaries to make it suitable as a sizing agent for glass fiber yarn for high-density weaving.

[0005] CN101880964A reports an environmentally friendly green electronic-grade glass fiber cloth secondary sizing. The invention mixes modified starch (brand name PVS300) with oily substances, water-based epoxy resin and polyethylene glycol methyl ether, etc., and then sizes the glass fiber yarn. The sizing has good coating properties on the glass fiber yarn, can reduce the generation of broken silk and hairiness of the glass fiber yarn during weaving, and the desizing and cleaning procedures are simple and environmentally friendly. On the basis of the existing secondary sizing technology, the appearance quality of the cloth surface is improved, the warp width is increased, and the effect of energy saving and environmental protection is achieved. The sizing of the invention is suitable for the warp sizing of electronic-grade glass fiber cloth for high-precision, high-uniformity, and high-performance printed circuit boards. The electronic-grade glass fiber cloth produced using this sizing formula has excellent cloth surface appearance quality, thinner cloth surface thickness, and the production process is energy-saving and environmentally friendly. However, the slurry is designed for electronic-grade glass fiber cloth used as a reinforcing material for circuit boards. The lower the requirement for the bundling of the yarn, the more conducive it is to increase the width of the warp yarn, and to avoid the infiltration of the glass fiber cloth in the CCL client resin and the resulting abnormalities such as lack of glue in the glass fiber yarn bundle, which causes a short circuit in the circuit board. Therefore, the slurry disclosed in CN101880964A cannot meet the requirements for stronger bundling of high-density weaving glass fiber yarn sizing. The requirements for high bundling, high wear resistance, high elasticity and excellent softness of high-density weaving glass fiber warp yarn are higher than those of electronic-grade glass fiber cloth, and the processing difficulty is greater.

[0006] CN115536791A reports a method for preparing starch slurry with two diblock polymer chains connected to the same substituent. The prepared starch slurry with two diblock polymer chains connected to the same substituent has significantly more significant adhesion to polyester-cotton yarn and cotton yarn than starch slurry and acid-hydrolyzed starch prepared by conventional technology. The adhesion performance gradually increases with the increase of grafting rate, and is very suitable for sizing polyester-cotton and cotton yarn. However, as shown in Comparative Example 3 of the present application, the performance of the starch slurry applied to sizing of high-density weaving glass fiber yarn is very unsatisfactory. Summary of the invention

[0007] [Technical issues]

[0008] Provided are an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarns with starch as the main film-forming agent and a preparation method thereof. The slurry has suitable viscosity and surface tension and excellent slurry stability, and is applied to sizing high-density weaving glass fiber yarns to achieve excellent sizing performance: the sizing rate is high and the processed product has high bundling, high wear resistance, high elasticity, excellent mechanical properties and excellent softness.

[0009] [Technical solution]

[0010] On the one hand, a method for preparing a starch slurry for sizing high-density glass fiber yarn for weaving is provided, which comprises the following steps:

[0011] (1) The preparation of amphiphilic starch comprises the following steps: starch refining, starch acid hydrolysis, hydrophobic modification and functional monomer modification, wherein:

[0012] The hydrophobic modification step comprises: preparing starch emulsion 1 from the acid-hydrolyzed starch obtained by starch refining and starch acid hydrolysis treatment; adding vinyl trimethoxy silane to the starch emulsion 1 in an inert gas atmosphere and a water bath at 50 to 70° C., adjusting the pH value of the system to 11 to 12 for reaction, wherein in the reaction system, the mass fraction of the acid-hydrolyzed starch is 25 to 40%, the mass fraction of the vinyl trimethoxy silane is 0.5 to 2%, and the reaction is completed after 4 to 6 hours to obtain modified starch A;

[0013] The functional monomer modification step comprises: preparing modified starch A into starch emulsion II, adding 3-chloro-2-hydroxypropyltrimethylammonium chloride and sodium hydroxide to starch emulsion II in an inert gas atmosphere at 50-70° C. for reaction, wherein in the reaction system, the mass fraction of modified starch A is 25-40%, the mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride is 0.5-2%, and the molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to sodium hydroxide is 1:1; the reaction is completed after 4-8 hours to obtain amphiphilic starch;

[0014] (2) Starch gelatinization: the amphiphilic starch is prepared into an emulsion, stirred at 90 to 95° C. for 30 to 60 minutes to obtain a starch slurry;

[0015] (3) Slurry preparation: Add a plasticizer, a binder, a wetting agent and an antistatic agent to the starch slurry prepared in step (2), mix at 90-95° C., and cool to 60° C. to obtain an environmentally friendly starch slurry for sizing high-density glass fiber yarn for weaving; wherein:

[0016] The plasticizer includes: at least one of glycerol, dimethyl sulfate, dimethyl phosphate, diethyl phosphate, butyl phosphate, tributyl phosphate, isopropyl phosphate, triphenyl phosphate, dioctyl phthalate, tris(2-chloroethyl) phosphate, tris(2-ethylhexyl) phosphate, ethyl acetate, butyl acetate, trimethyl citrate, triethyl citrate, tributyl citrate, propyl citrate, acetylcitrate triethyl, acetylcitrate tributyl, ethyl stearate, dibutyl phthalate, ethyl nonanoate or ethyl oleate;

[0017] The binder comprises: at least one of methyltrimethoxysilane, dimethyldimethoxysilane, amyltrimethoxysilane, methyltriethoxysilane, isobutyltriethoxysilane, octyltriethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, diphenyldimethoxysilane, methylphenyldimethoxysilane, γ-aminopropyltriethoxysilane, aminophenyltrimethoxysilane, vinyltriisopropoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltriacetoxysilane, vinyltri-tert-butoxysilane, polyurethane siloxane or silane coupling agent KH-560;

[0018] Wetting agents include: ethoxylated soybean alcohol, ethoxylated rice bran alcohol, ethoxylated cetyl alcohol, ethoxylated isostearyl alcohol, ethoxylated oleyl alcohol, ethoxylated lanolin alcohol, ethoxylated cetyl alcohol, ethoxylated sunflower oil alcohol, ethoxylated coconut alcohol, ethoxylated castor alcohol, ethoxylated almond alcohol, ethoxylated grape seed alcohol, ethoxylated olive oil alcohol, ethoxylated avocado alcohol, ethoxylated tea tree alcohol, ethoxylated betaine, fatty alcohol polyoxyethylene ether, lauryl alcohol polyoxyethylene ether, stearyl alcohol polyoxyethylene ether At least one of ethylene oxide, linseed oil polyoxyethylene ether, castor oil polyoxyethylene ether, coconut alcohol polyoxyethylene ether, palm oil polyoxyethylene ether, soybean oil polyoxyethylene ether, sunflower oil polyoxyethylene ether, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, bisphenol A polyoxyethylene ether, alkylphenol polyoxyethylene ether, p-tert-butylphenol polyoxyethylene ether, p-octylphenol polyoxyethylene ether, p-nonylphenol polyoxyethylene ether, p-phenylphenol polyoxyethylene ether, p-thiophenol polyoxyethylene ether, oleic acid polyoxyethylene ether or diphenyl ether polyoxyethylene ether;

[0019] The antistatic agent includes at least one of sodium polyacrylate, sodium polyoxyethylene fatty alcohol sulfate, sodium dodecylbenzene sulfonate, octadecyltrimethylammonium chloride, dodecyl betaine or Span 80.

[0020] In some embodiments, the combustion ash of the amphiphilic starch is below 0.35%, and the static surface tension of a 1% by mass amphiphilic starch aqueous solution at room temperature is less than 45 mPa.s.

[0021] In some embodiments, the mass fraction of the plasticizer in the environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is 1-2%.

[0022] In some embodiments, the mass fraction of the binder in the environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is 0.5-1%.

[0023] In some embodiments, the mass fraction of the wetting agent in the environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is 0.01-0.05%.

[0024] In some embodiments, the mass fraction of the antistatic agent in the environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is 0.1-0.5%.

[0025] In some embodiments, the mass fraction of the amphiphilic starch in the environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is 5.5-7.5%.

[0026] In some embodiments, the environmentally friendly starch slurry for sizing the high-density weaving glass fiber yarn adopts one of the following formulas:

[0027] (a) the plasticizer is glycerol, the binder is methyl triethoxy silane, the wetting agent is ethoxylated soybean alcohol, and the antistatic agent is sodium polyacrylate;

[0028] (b) the plasticizer is dimethyl sulfate, the binder is polyurethane siloxane; the wetting agent is ethoxylated betaine; and the antistatic agent is sodium fatty alcohol polyoxyethylene sulfate;

[0029] (c) the plasticizer is dimethyl phosphate, the binder is vinyl trimethoxy silane, the wetting agent is ethoxylated rice bran alcohol, and the antistatic agent is sodium dodecylbenzene sulfonate;

[0030] (d) the plasticizer is ethyl acetate, the binder is methyltriethoxysilane, the wetting agent is lauryl alcohol polyoxyethylene ether, and the antistatic agent is octadecyltrimethylammonium chloride;

[0031] (e) The plasticizer is triethyl citrate, the binder is silane coupling agent KH-560, the wetting agent is linseed oil polyoxyethylene ether, and the antistatic agent is dodecyl betaine.

[0032] On the other hand, an environmentally friendly starch sizing material for sizing high-density glass fiber yarn for weaving prepared by the aforementioned method is provided.

[0033] On the other hand, the invention provides the use of the aforementioned environmentally friendly starch sizing material for sizing high-density weaving glass fiber yarns in sizing high-density weaving glass fiber yarns.

[0034] [Beneficial Effects]

[0035] Different from the traditional starch slurry, which contains a large amount of polyvinyl alcohol and surfactant in the formula to form good adhesion with glass fiber yarn, and will generate a large amount of foam when the slurry is prepared, the present invention designs and develops a preparation method of an environmentally friendly slurry for sizing glass fiber warp yarn for high-density weaving, by modifying starch and introducing a structure similar to that of surfactant into starch molecules, that is, using specific amphiphilic starch, while improving the adhesion to glass fiber yarn, the surface tension of starch slurry is reduced, thereby reducing the amount of textile auxiliaries, and improving the sizing performance of the slurry while also improving the foam problem;

[0036] The present invention prepares a sizing material for glass fiber warp yarn sizing with high bundling property and suitable for high-density weaving by combining specific amphiphilic starch with suitable textile auxiliaries; the specific amphiphilic starch has both hydrophilic functional groups and hydrophobic functional groups, wherein the hydrophobic functional groups are obtained by grafting and modifying with a silane coupling agent; the amphiphilic structure gives the starch high surface activity, reduces its surface tension, and increases its permeability to glass fiber, while the addition of the silane coupling agent increases the adhesion of the starch sizing material to the glass fiber; on the basis of the specific amphiphilic starch, appropriate amounts of plasticizers, binders, wetting agents and antistatic agents are added as textile auxiliaries, and the obtained sizing material can simultaneously meet the requirements of high bundling property, high wear resistance and high adhesion for high-density woven glass fiber warp yarn after sizing. The starch slurry formula has excellent elasticity, excellent mechanical properties (high elongation at break) and excellent softness. The designed starch slurry formula can be applied to the sizing of high-density woven glass fiber warp yarns. While meeting the high bundling property, starch is used to replace polyvinyl alcohol, which not only conforms to the green development concept but also meets the requirements of subsequent weaving use of glass fiber yarns. The present invention provides an environmentally friendly starch slurry for sizing high-density woven glass fiber yarns with starch as the main film-forming agent and a preparation method thereof. The slurry has suitable viscosity and surface tension, excellent slurry stability, and is applied to the sizing of high-density woven glass fiber yarns to achieve excellent sizing performance: the sizing rate is high and the processed product has high bundling property, high wear resistance, high elasticity, excellent mechanical properties and excellent softness.

[0037] The advantages of the present invention are as follows:

[0038] (1) High bundling property: The present invention uses amphiphilic starch in combination with other textile auxiliaries to tightly bond the fibers together inside the glass fiber warp yarn and form a relatively complete size film on the surface of the glass fiber, thereby greatly improving the bundling property of the glass fiber warp yarn and reducing the warp yarn width;

[0039] (2) Desizing: The main film-forming agent of the starch slurry of the present invention is amphiphilic starch, which can reduce the desizing temperature and shorten the desizing time during desizing, which not only ensures the strength loss of the glass fiber warp yarn, but also reduces energy consumption. At the same time, compared with the traditional slurry, the ash content of the starch slurry of the present invention after desizing is less than 0.35%, and sufficient combustion reduces the appearance of black spots and yellow spots, thereby improving the surface quality of the glass fiber cloth after weaving;

[0040] (3) Excellent mechanical properties: The starch slurry of the present invention has excellent film properties. When the starch slurry is used to size the glass fiber warp yarn, the wear resistance and elongation at break of the glass fiber warp yarn are not only enhanced, but also the surface properties thereof are effectively improved, thereby improving the mechanical properties of the glass fiber warp yarn.

[0041] (4) Excellent slurry stability: The amphiphilic starch of the present invention introduces the concept of surfactant into starch slurry. By simultaneously introducing hydrophilic groups and lipophilic groups into the starch molecular chain, the starch macromolecules exhibit typical structural characteristics of surfactants, and the emulsification stability of the starch slurry is significantly improved. By combining with suitable textile auxiliaries, the prepared slurry has no obvious precipitation after being placed at room temperature for at least 36 hours.

[0042] (5) Environmental protection: The invention adopts widely renewable starch as the main film-forming agent. The invention is in line with the current concept of green development and efficient resource utilization. During the use of starch slurry, the slurry tank is easy to clean with low energy consumption. In addition, less toxic gas is released during the calcination process, and the pollution to the environment is also reduced accordingly. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 These are SEM images of the original yarn, the glass fiber warp yarn after sizing in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0044] In the present invention, unless otherwise specified, all parts and percentages are expressed in mass units, and the equipment and raw materials used can be purchased from the market or are common in the art. The methods in the following examples are all conventional methods in the art unless otherwise specified.

[0045] Example 1

[0046] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn comprises the following steps:

[0047] (1) The preparation of amphiphilic starch includes the following steps: starch refining, starch acid hydrolysis, hydrophobic modification and functional monomer modification, as follows:

[0048] Step 1.1, starch refining: the starch is evenly dispersed in a methanol-deionized water solution (the volume ratio of methanol to water is 15:85) to prepare a starch milk with a mass fraction of 40%; after mechanical stirring at 50° C. for 1 hour, the starch is filtered, and the obtained filter cake is washed, dried, and ground into powder to obtain refined starch;

[0049] Step 1.2, starch acid hydrolysis: disperse the refined starch prepared in step 1.1 in deionized water to prepare a starch milk with a mass fraction of 40%; mechanically stir at 50° C., and drop 95 mL of a 2 mol / L dilute hydrochloric acid solution into the starch milk. After reacting for 4 hours, neutralize the starch milk with a sodium carbonate solution, and filter, wash, dry, and grind the starch milk into powder to obtain acid-hydrolyzed starch;

[0050] Step 1.3, hydrophobic modification: the acid-hydrolyzed starch prepared in step 1.2 is dispersed in deionized water to prepare starch milk; the starch milk is placed in a four-necked flask, in a nitrogen atmosphere and a water bath at 50°C, vinyltrimethoxysilane is added, and the pH value of the system is adjusted to 11-12 with a 5% by mass sodium hydroxide solution to carry out a reaction, wherein the mass fraction of starch in the reaction system is 25%, and the mass fraction of vinyltrimethoxysilane is 0.5%. The reaction is completed after 4 hours, and the resultant is filtered, washed, dried, and ground into powder to obtain modified starch A;

[0051] Step 1.4, functional monomer modification: the modified starch A prepared in step 1.3 is dispersed in deionized water to prepare starch milk, the starch milk is placed in a four-necked flask, and 3-chloro-2-hydroxypropyltrimethylammonium chloride and sodium hydroxide are added to react in a nitrogen atmosphere and a water bath at 50°C, wherein the mass fraction of starch in the reaction system is 25%, the mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride is 0.5%, and the molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to sodium hydroxide is 1:1; the reaction is completed after 6 hours, and the resultant is filtered, washed, dried, and ground into powder to obtain modified starch B; thereby obtaining amphiphilic starch (the combustion ash of amphiphilic starch is below 0.35%, and the static surface tension of an amphiphilic starch aqueous solution with a mass fraction of 1% under normal temperature conditions is <45mPa.s);

[0052] (2) Starch gelatinization: Pour the main film-forming agent amphiphilic starch into a pulp boiling barrel, add deionized water to prepare an emulsion, stir and heat to 90°C, stir at 90°C for 30 minutes, then add deionized water to obtain a starch slurry;

[0053] (3) Slurry preparation: Add a plasticizer (propylene glycol), a binder (methyl triethoxysilane), a wetting agent (ethoxylated soybean alcohol, peroxide value of 5 meg / kg) and an antistatic agent (sodium polyacrylate, molecular weight 8000-12000, solid content between 40% and 50%) to the starch slurry prepared in step (2), stir at 90° C. for 15 minutes, cool to 60° C., and obtain an environmentally friendly starch slurry for sizing high-density glass fiber yarn for weaving (the formulation of each component is shown in Table 1), which is stored in a slurry storage barrel for use.

[0054] Table 1

[0055]

[0056] Note: The amount of each component is the mass percentage concentration, and “-” means that the corresponding component is not contained.

[0057] Example 2

[0058] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn, referring to Example 1, except that the types and amounts of the plasticizer, binder, wetting agent, and antistatic agent in step (3) are adjusted (as shown in Table 1), wherein:

[0059] Plasticizer: dimethyl sulfate;

[0060] Binder: polyurethane siloxane (solid content 25%-35%);

[0061] Wetting agent: ethoxylated betaine (solid content 15%-25%);

[0062] Antistatic agent: sodium polyoxyethylene fatty alcohol sulfate (purity 99%).

[0063] Example 3

[0064] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn, referring to Example 1, except that the amount of amphiphilic starch in step (2) (as shown in Table 1) is adjusted, and the types and amounts of plasticizer, binder, wetting agent, and antistatic agent in step (3) (as shown in Table 1) are adjusted, wherein:

[0065] Plasticizer: dimethyl phosphate;

[0066] Binder: vinyltrimethoxysilane;

[0067] Wetting agent: ethoxylated rice bran alcohol (purity 99%);

[0068] Antistatic agent: sodium dodecylbenzene sulfonate (solid content 25%-35%).

[0069] Example 4

[0070] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn, referring to Example 1, except that the amount of amphiphilic starch in step (2) (as shown in Table 1) is adjusted, and the types and amounts of plasticizer, binder, wetting agent, and antistatic agent in step (3) (as shown in Table 1) are adjusted, wherein:

[0071] Plasticizer: ethyl acetate;

[0072] Binder: methyltriethoxysilane;

[0073] Wetting agent: lauryl alcohol polyoxyethylene ether (solid content 15%-25%);

[0074] Antistatic agent: octadecyltrimethylammonium chloride (purity 70%).

[0075] Example 5

[0076] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn, referring to Example 1, except that the amount of amphiphilic starch in step (2) (as shown in Table 1) is adjusted, and the types and amounts of plasticizer, binder, wetting agent, and antistatic agent in step (3) (as shown in Table 1) are adjusted, wherein:

[0077] Plasticizer: triethyl citrate;

[0078] Binder: silane coupling agent KH-560;

[0079] Wetting agent: linseed oil polyoxyethylene ether (solid content 15%-25%);

[0080] Antistatic agent: dodecyl betaine (purity 70%).

[0081] Comparative Example 1

[0082] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is described with reference to Example 1, except that:

[0083] The types and amounts of plasticizers, binders, wetting agents, and antistatic agents in step (3) are adjusted with reference to the literature "Application Research of Modified Domestic Starch Wetting Agents", wherein:

[0084] Plasticizer: polyethylene glycol PEG4000;

[0085] Binder: water-soluble epoxy resin E-801;

[0086] Wetting agent: NBL-E-201;

[0087] Antistatic agent: GF-100.

[0088] Comparative Example 2

[0089] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is described with reference to Example 1, except that the amphiphilic starch is replaced by unmodified native starch.

[0090] Comparative Example 3

[0091] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is described with reference to Example 1, except that the amphiphilic starch is replaced with other types of amphiphilic starch reported previously (such as Example 3 of patent CN115536791A).

[0092] Comparative Example 4

[0093] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is described with reference to Example 1, except that no plasticizer is added.

[0094] Comparative Example 5

[0095] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is described with reference to Example 1, except that no binder is added.

[0096] Comparative Example 6

[0097] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is described with reference to Example 1, except that no wetting agent is added.

[0098] Comparative Example 7

[0099] A method for preparing an environmentally friendly starch slurry for sizing high-density weaving glass fiber yarn is described with reference to Example 1, except that no antistatic agent is added.

[0100] Comparative Example 8

[0101] Commercially available starch size for sizing glass fiber yarn: Dongmei brand oxidized composite modified starch (model -908).

[0102] Preparation method of slurry: slowly add Dongmei brand oxidized composite modified starch (model-908) into 40℃ water to obtain a starch emulsion with a solid content of 40%, heat it to 90℃ while stirring, stir until it is completely dissolved, add water to adjust the starch concentration to 20%, gelatinize for 1h and put it into a slurry storage barrel for use. When sizing, dilute it to a slurry concentration of 6% for sizing experiments.

[0103] Application Examples

[0104] The environmentally friendly starch sizing agent for sizing high-density weaving glass fiber yarn prepared in the above-mentioned embodiments and comparative examples is used in sizing high-density weaving glass fiber yarn. The high-density weaving glass fiber yarn used is 45-count 2-ply glass fiber yarn provided by Yushun Textile Co., Ltd. The sizing process includes the following steps:

[0105] A GA392 electronic single yarn sizing machine was used for sizing tests. The sizing tank temperature was set to 65°C, the pre-drying temperature was set to 100°C, and the drying temperature was set to 120°C. The prepared slurry was poured into the sizing tank, and the glass fiber yarn was wound on the sizing machine for sizing. The sizing speed was 15m / min, and the sizing tension was 0.6N. After sizing, the yarn tube was taken out to obtain the product.

[0106] Test Case

[0107] According to the method of the application example, the starch slurry prepared in each embodiment and comparative example was used to size the glass fiber yarn, and the sizing rate and product performance were tested; the stability of the starch slurry used for sizing the glass fiber yarn for high-density weaving was tested.

[0108] Sizing rate: Tested by desizing method;

[0109] Friction fracture times: Use the wear tester test method to refer to the standard FZ / T01058-1999 "Yarn wear test method reciprocating grinding roller method" to test the wear resistance of the product, and use the friction fracture times as the wear resistance performance index;

[0110] Breaking strength: refer to GB / T 7690.3-2013 Determination method of breaking strength of textile glass fiber yarn;

[0111] Elongation at break: Refer to GB / T 7690.3-2013 Determination method for elongation at break of textile glass fiber yarn;

[0112] Slurry stability: Keep the starch slurry at 60℃ for a period of time and observe whether the slurry has precipitation, etc. The stability of the slurry is determined by the room temperature stability time.

[0113] Slurry viscosity: Put the prepared starch slurry into NDJ-79 rotary viscometer, calibrate and adjust the rotary viscometer to zero, and test its viscosity in the viscometer at 95℃. Repeat the test twice for each sample, record the readings and calculate the average viscosity. The unit of viscosity is mPa﹒s;

[0114] Surface tension of slurry: dilute the prepared starch slurry to a mass fraction of 1%. Take a starch slurry sample after the temperature reaches room temperature. Use a DCAT-11 surface tension meter to test the surface tension of the sample. Repeat 3 times for each sample and take the average value.

[0115] Combustion ash: The ash determination method refers to GB / T22427.1-2008 "Determination of starch ash content". Put the pre-ashed starch slurry into the crucible, move the crucible into the muffle furnace, raise the temperature to 800℃, and maintain this temperature until all the remaining carbon disappears. Open the furnace door, move the crucible to the furnace mouth and cool it to about 200℃, then quickly move the crucible into the dryer to cool it to room temperature, and weigh it accurately (accurate to 0.0001g). Repeat until constant weight.

[0116] The test results are summarized in Table 2.

[0117] Table 2

[0118]

[0119]

[0120] The bundling properties of the original yarn, the sizing of the glass fiber warp yarn of Example 1 and the comparative example 1 were observed by scanning electron microscope. The results are as follows: Figure 1 As shown in the figure, it can be seen from the comparison that the glass fiber warp yarn sized with the starch slurry of Example 1 has higher bundling property than the original yarn and the comparative example 1. Therefore, the starch slurry of Example 1 is more suitable for sizing the glass fiber yarn for high-density weaving.

[0121] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing a starch slurry for sizing high-density weaving glass fiber yarn, characterized in that: The steps include: (1) The preparation of amphiphilic starch comprises the following steps: starch refining, starch acid hydrolysis, hydrophobic modification and functional monomer modification, wherein: The hydrophobic modification step comprises: preparing starch emulsion 1 from the acid-hydrolyzed starch obtained by starch refining and starch acid hydrolysis treatment; adding vinyl trimethoxy silane to the starch emulsion 1 in an inert gas atmosphere and a water bath at 50 to 70° C., adjusting the pH value of the system to 11 to 12 for reaction, wherein in the reaction system, the mass fraction of the acid-hydrolyzed starch is 25 to 40%, the mass fraction of the vinyl trimethoxy silane is 0.5 to 2%, and the reaction is completed after 4 to 6 hours to obtain modified starch A; The functional monomer modification step comprises: preparing modified starch A into starch emulsion II, adding 3-chloro-2-hydroxypropyltrimethylammonium chloride and sodium hydroxide to starch emulsion II in an inert gas atmosphere at 50-70° C. for reaction, wherein in the reaction system, the mass fraction of modified starch A is 25-40%, the mass fraction of 3-chloro-2-hydroxypropyltrimethylammonium chloride is 0.5-2%, and the molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride to sodium hydroxide is 1:1; the reaction is completed after 4-8 hours to obtain amphiphilic starch; (2) starch gelatinization: preparing the amphiphilic starch into an emulsion, heating and stirring to gelatinize, and obtaining a starch slurry; (3) Slurry preparation: Add a plasticizer, a binder, a wetting agent and an antistatic agent to the starch slurry prepared in step (2), heat and mix, and cool to obtain an environmentally friendly starch slurry for sizing high-density glass fiber yarn for weaving; wherein: The plasticizer includes: at least one of glycerol, dimethyl sulfate, dimethyl phosphate, diethyl phosphate, butyl phosphate, tributyl phosphate, isopropyl phosphate, triphenyl phosphate, dioctyl phthalate, tris(2-chloroethyl) phosphate, tris(2-ethylhexyl) phosphate, ethyl acetate, butyl acetate, trimethyl citrate, triethyl citrate, tributyl citrate, propyl citrate, acetylcitrate triethyl, acetylcitrate tributyl, ethyl stearate, dibutyl phthalate, ethyl nonanoate or ethyl oleate; The binder comprises: at least one of methyltrimethoxysilane, dimethyldimethoxysilane, amyltrimethoxysilane, methyltriethoxysilane, isobutyltriethoxysilane, octyltriethoxysilane, ethyltriethoxysilane, vinyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, diphenyldimethoxysilane, methylphenyldimethoxysilane, γ-aminopropyltriethoxysilane, aminophenyltrimethoxysilane, vinyltriisopropoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltriacetoxysilane, vinyltri-tert-butoxysilane, polyurethane siloxane or silane coupling agent KH-560; Wetting agents include: ethoxylated soybean alcohol, ethoxylated rice bran alcohol, ethoxylated cetyl alcohol, ethoxylated isostearyl alcohol, ethoxylated oleyl alcohol, ethoxylated lanolin alcohol, ethoxylated cetyl alcohol, ethoxylated sunflower oil alcohol, ethoxylated coconut alcohol, ethoxylated castor alcohol, ethoxylated almond alcohol, ethoxylated grape seed alcohol, ethoxylated olive oil alcohol, ethoxylated avocado alcohol, ethoxylated tea tree alcohol, ethoxylated betaine, fatty alcohol polyoxyethylene ether, lauryl alcohol polyoxyethylene ether, stearyl alcohol polyoxyethylene ether At least one of ethylene oxide, linseed oil polyoxyethylene ether, castor oil polyoxyethylene ether, coconut alcohol polyoxyethylene ether, palm oil polyoxyethylene ether, soybean oil polyoxyethylene ether, sunflower oil polyoxyethylene ether, nonylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, bisphenol A polyoxyethylene ether, alkylphenol polyoxyethylene ether, p-tert-butylphenol polyoxyethylene ether, p-octylphenol polyoxyethylene ether, p-nonylphenol polyoxyethylene ether, p-phenylphenol polyoxyethylene ether, p-thiophenol polyoxyethylene ether, oleic acid polyoxyethylene ether or diphenyl ether polyoxyethylene ether; The antistatic agent includes at least one of sodium polyacrylate, sodium polyoxyethylene fatty alcohol sulfate, sodium dodecylbenzene sulfonate, octadecyltrimethylammonium chloride, dodecyl betaine or Span 80.

2. The method according to claim 1, characterized in that The combustion ash content of the amphiphilic starch is below 0.35%, and the static surface tension of an amphiphilic starch aqueous solution with a mass fraction of 1% under normal temperature conditions is less than 45 mPa.s.

3. The method according to claim 1, characterized in that The mass fraction of the plasticizer in the environmentally friendly starch sizing agent for sizing the glass fiber yarn for high-density weaving is 1-2%.

4. The method according to claim 1, characterized in that The mass fraction of the binder in the environmentally friendly starch sizing agent for sizing the glass fiber yarn for high-density weaving is 0.5-1%.

5. The method according to claim 1, characterized in that The mass fraction of the wetting agent in the environmentally friendly starch sizing material for sizing glass fiber yarn for high-density weaving is 0.01-0.05%.

6. The method according to claim 1, characterized in that The mass fraction of the antistatic agent in the environmentally friendly starch sizing material for sizing glass fiber yarn for high-density weaving is 0.1-0.5%.

7. The method according to claim 1, characterized in that The mass fraction of amphiphilic starch in the environmentally friendly starch sizing agent for sizing glass fiber yarn for high-density weaving is 5.5-7.5%.

8. The method according to claim 1, characterized in that In some embodiments, the environmentally friendly starch slurry for sizing the high-density weaving glass fiber yarn adopts one of the following formulas: (a) the plasticizer is glycerol, the binder is methyl triethoxysilane, the wetting agent is ethoxylated soybean alcohol, and the antistatic agent is sodium polyacrylate; (b) the plasticizer is dimethyl sulfate, the binder is polyurethane siloxane; the wetting agent is ethoxylated betaine; and the antistatic agent is sodium fatty alcohol polyoxyethylene sulfate; (c) the plasticizer is dimethyl phosphate, the binder is vinyl trimethoxy silane, the wetting agent is ethoxylated rice bran alcohol, and the antistatic agent is sodium dodecylbenzene sulfonate; (d) the plasticizer is ethyl acetate, the binder is methyltriethoxysilane, the wetting agent is lauryl alcohol polyoxyethylene ether, and the antistatic agent is octadecyltrimethylammonium chloride; (e) The plasticizer is triethyl citrate, the binder is silane coupling agent KH-560, the wetting agent is linseed oil polyoxyethylene ether, and the antistatic agent is dodecyl betaine.

9. An environmentally friendly starch sizing material for sizing high-density weaving glass fiber yarns obtained by the method of any one of claims 1 to 8.

10. Use of the environmentally friendly starch sizing material for sizing high-density weaving glass fiber yarns as claimed in claim 9 in sizing high-density weaving glass fiber yarns.

Citation Information

Patent Citations

  • Environment-friendly and green secondary slurry of electronic-grade glass fiber cloth

    CN101880964A

  • Cation modified starch, preparation method and applications thereof

    CN104119455A

  • Hydrophilic-lipophilic modified starch slurry and preparation method thereof

    CN109232752A

  • Starch type impregnating compound for electronic yarns as well as preparation method and application thereof

    CN111943527A

  • Preparation method of textile sizing agent

    CN112593404A